Rabies virus modifies host behaviour through a snake-toxin like region of its glycoprotein that inhibits neurotransmitter receptors in the CNS. Issue 1 (December 2017) - Hueffer, Karsten; Khatri, Shailesh; Rideout, Shane; Harris, Michael; Papke, Roger; Stokes, Clare; Schulte, Marvin
Abstract Rabies virus induces drastic behaviour modifications in infected hosts. The mechanisms used to achieve these changes in the host are not known. The main finding of this study is that a region in the rabies virus glycoprotein, with homologies to snake toxins, has the ability to alter behaviour in animals through inhibition of nicotinic acetylcholine receptors present in the central nervous system. This finding provides a novel aspect to virus receptor interaction and host manipulation by pathogens in general. The neurotoxin-like region of the rabies virus glycoprotein inhibited acetylcholine responses of α4β2 nicotinic receptorsin vitro, as did full length ectodomain of the rabies virus glycoprotein. The same peptides significantly altered a nicotinic receptor induced behaviour inC. elegans and increased locomotor activity levels when injected into the central nervous system of mice. These results provide a mechanistic explanation for the behavioural changes in hosts infected by rabies virus.